Finding out fast about the impact of Covid-19: The need for policy-relevant methodological innovation. (April 2021) - Rahman, Hossain Zillur; Matin, Imran; Banks, Nicola; Hulme, David
Highlights: The Covid-19 crisis has made the development of innovative, rapid survey methodologies a research priority. Replacing face-to-face surveys with mobile surveys is feasible but requires access to pre-existing sampling frames. Researchers must rethink short-term policy engagement and impact planning alongside longer-term discourse-shaping strategies. Research leadership from the Global South is essential for research to achieve impact on short and long term national policy. Abstract: In this viewpoint we explore one joint research initiative in Bangladesh to illustrate how methodological innovations using mobile phone technologies and pre-existing survey databases can generate rapid and insightful data on the impacts of the Covid-19 pandemic with significant policy influence. Situating this innovation within theoretical and methodological antecedents for rapid appraisal, we show how strong local ownership can facilitate innovation, rapid research and strong policy engagement amidst even the most difficult research conditions. Such rapid surveys and analysis must remain a research priority in times of crisis. Academic researchers in partner organisations further afield must ask important questions around how they can best support such locally-led research initiatives: in preparing for, analysing or writing up the research or in joining efforts to communicate them to wider communities of policy-makers and practitioners globally.